2021
DOI: 10.5812/aapm.117140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Atorvastatin Administration on the Outcomes of Patients with Traumatic Brain Injury: A Double-blinded Randomized Clinical Trial

Abstract: Background: Traumatic brain injury (TBI) is one of the common causes of long-term disabilities and mortality. This study aimed to evaluate the effect of atorvastatin administration on the Glasgow Coma Scale (GCS), Glasgow Outcome Scale (GOS), and Disability Rating Scale (DRS) in patients with TBI. Methods: This double-blinded randomized clinical trial included 60 patients with TBI in Golestan Hospital of Ahvaz, Iran. After obtaining an informed consent from all patients, the patients were randomly assigned int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…No adverse effects were reported in this research. 4 The medication was given to each individual within 10 h of the accident in both research. 4 , 11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No adverse effects were reported in this research. 4 The medication was given to each individual within 10 h of the accident in both research. 4 , 11 …”
Section: Resultsmentioning
confidence: 99%
“…In clinical management, statin use should not be discontinued after TBI. Soltani et al 4 2021 Evaluation of the Effect of Atorvastatin Administration on the Outcomes of Patients with Traumatic Brain Injury: A Double-blinded Randomized Clinical Trial Randomized controlled trial 60 The results revealed the positive effect of atorvastatin on the improvement of outcomes measurements such as GCS, DRS, and GOS in patients after moderate and severe TBI. Khokhar et al 5 2018 Mortality and Associated Morbidities Following Traumatic Brain Injury in Older Medicare Statin Users Retrospective cohort study 100.515 When appropriate, atorvastatin and simvastatin can be considered to older adults with TBI in order to decrease mortality and associated morbidities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the fact that several new lipid-lowering medications have been introduced in the past decade [26][27][28], statins still remain as the most widely used class of medications prescribed for atherosclerotic cardiovascular disease hyperlipidemia [29,30]. Statins have interesting pleiotropic properties [31][32][33][34][35][36][37][38][39][40], which attract the attention of researchers to use them as potential drugs for improving the recovery and reducing the severity of TBI [29,41,42]. According to Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical and clinical research was accomplished to survey the impact of statins on TBI. For instance, two randomized clinical trials (RCT) demonstrated that atorvastatin and simvastatin could significantly improve the Glasgow Coma Scale (GCS) and Disability Rating Scale (DRS) test after one to three months and ameliorate Glasgow Outcome Scale (GOS) in the first month of post-intervention [41]. Other research on the TBI mouse model reported that statins could effectively improve post-TBI neuroinflammation through alternative polarization of microglia/macrophages and changing peripheral leukocyte invasion [42].…”
Section: Introductionmentioning
confidence: 99%